PHYSIO-BIOLOGICAL MARKERS IN ZINC-INDUCED MOULTED AND NON-MOULTED WHITE LEGHORN LAYERS (GALLUS DOMESTICUS) - M. Idris; F. Muhammad; H. Anwar; U. Farooq; M. A. Anjum; H. Rashid (Journal of Animal and Plant Sciences, 2023)
Various approaches for the induction of moulting have been explained in the literature review, however, there is a dire need to explore other effective methods that can be more efficient in terms of production performance. The current study was conducted to evaluate the role of zinc-induced moulting on certain body performance attributes, serum biochemical profile and serum hormonal profile of White Leghorn layers towards the end of their first production cycle (spent layers). Commercial White Leghorn birds (n=24) of 67-weeks of age were procured from local market and were induced to moult with zinc oxide (3 g/kg diet) for three consecutive weeks. The spent layers were grouped as non-moulted group (NML) and moulted group (ML) after zinc-induced moulting. The result on overall body performance attributes indicated that the body weight and weight of organs significantly (P≤0.05) decreased in ML group birds as compared to the birds of NML group except for kidneys. The cholesterol, HDL, LDL and triglycerides were lower (P≤0.05) in birds of ML group as compared to birds of NML. On the contrary, serum circulating levels of ALT and AST were statistically higher (P≤0.05) in birds of ML group as compared to their counterpart NML group. A significant increase (P≤0.05) was noticed in serum T4 and cortisol concentrations for birds of ML group as compared to those of NML group, whereas T3 level was found decreased (P≤0.05) in birds of ML group. The results of present study indicated that usage of dietary supplementation of ZnO (3g/kg), for the purpose of moulting, exhibits promising effects on body performance attributes and serum biomarkers. Different dietary concentrations of ZnO may be evaluated in future to minimize stress and further enhance the performance of spent layers.
Keywords: Cortisol; Moulting; Spent layers; Zinc-oxide